DEN1 deneddylates non-cullin proteins in vivo. - Chan, Y.; Yoon, J.; Wu, J.T.; Kim, H.J.; Pan, K.T.; Yim, J.; Chien, C.T. (Journal of Cell Science, 2008)
The ubiquitin-like protein Nedd8/Rub1 covalently modifies and activates cullin ubiquitin ligases. However, the repertoire of Nedd8-modified proteins and the regulation of protein neddylation status are not clear. The cysteine protease DEN1/NEDP1 specifically processes the Nedd8 precursor and has been suggested to deconjugate Nedd8 from cullin proteins. By characterizing the Drosophila DEN1 protein and DEN1 null (DEN1(null)) mutants, we provide in vitro and in vivo evidence that DEN1, in addition to processing Nedd8, deneddylates many cellular proteins. Although purified DEN1 protein efficiently deneddylates the Nedd8-conjugated cullin proteins Cul1 and Cul3, neddylated Cul1 and Cul3 protein levels are not enhanced in DEN1(null). Strikingly, many cellular proteins are highly neddylated in DEN1 mutants and are deneddylated by purified DEN1 protein. DEN1 deneddylation activity is distinct from that of the cullin-deneddylating CSN. Genetic analyses indicate that a balance between neddylation and deneddylation maintained by DEN1 is crucial for animal viability.